A Web-Based Integration Procedure for the Development of Reconfigurable Robotic Work-Cells. (19th July 2013) - Ferreira, Paulo; Reyes, Victoria; Mestre, João
Concepts related to the development of reconfigurable manufacturing systems (RMS) and methodologies to provide the best practices in the processing industry and factory automation, such as system integration and web-based technology, are major issues in designing next-generation manufacturing systems (NGMS). Adaptable and integrable devices are crucial for the success of NGMS. In robotic cells the integration of manufacturing components is essential to accelerate system adaptability. Sensors, control architectures and communication technologies have contributed to achieving further agility in reconfigurable factories. In this work a web-based robotic cell integration procedure is proposed to aid the identification of reconfigurable issues and requirements. This methodology is applied to an industrial robot manipulator to enhance system flexibility towards the development of a reconfigurable robotic platform.